(untitled) - Peng, Mike W.; Mike W. Peng (Boston, MA, 2006)
This book is unique in its thorough study of Mergers and Acquisitions (M&A) strategies. Global foreign direct investment continues to rise along with cross-border M&As . Increasingly, MNEs are investing a disproportionately higher amount of their resources in emerging economies, in essence, making their strategy more balanced and more global. This balanced understanding of international business is critical to discovering current cutting-edge practices in the field. The text examines the ramifications of a more balanced approach for multi-national enterprises
Keywords: Strategic planning; Business planning